The Benefits and Harms of Antibiotic Prophylaxis for Urinary Tract Infection in Older Adults. (17th February 2021) - Langford, Bradley J; Brown, Kevin A; Diong, Christina; Marchand-Austin, Alex; Adomako, Kwaku; Saedi, Arezou; Schwartz, Kevin L; Johnstone, Jennie; MacFadden, Derek R; Matukas, Larissa M; Patel, Samir N; Garber, Gary; et al.
Abstract: Background: The role of antibiotics in preventing urinary tract infection (UTI) in older adults is unknown. We sought to quantify the benefits and risks of antibiotic prophylaxis among older adults. Methods: We conducted a matched cohort study comparing older adults (≥66 years) receiving antibiotic prophylaxis, defined as antibiotic treatment for ≥30 days starting within 30 days of a positive culture, with patients with positive urine cultures who received antibiotic treatment but did not receive prophylaxis. We matched each prophylaxis recipient to 10 nonrecipients based on organism, number of positive cultures, and propensity score. Outcomes included (1) emergency department (ED) visit or hospitalization for UTI, sepsis, or bloodstream infection within 1 year; (2) acquisition of antibiotic resistance in urinary tract pathogens; and (3) antibiotic-related complications. Results: Overall, 4.7% (151/3190) of UTI prophylaxis patients and 3.6% (n = 1092/30 542) of controls required an ED visit or hospitalization for UTI, sepsis, or bloodstream infection (hazard ratio [HR], 1.33; 95% confidence interval [CI], 1.12–1.57). Acquisition of antibiotic resistance to any urinary antibiotic (HR, 1.31; 95% CI, 1.18–1.44) and to the specific prophylaxis agent (HR, 2.01; 95% CI, 1.80–2.24) was higher in patients receiving prophylaxis. While the overall risk of antibiotic-related complications was similar between groups (HR, 1.08; 95% CI, .94–1.22), the risk of Clostridioides difficile and general medication adverse events was higher in prophylaxis recipients (HR [95% CI], 1.56 [1.05–2.23] and 1.62 [1.11–2.29], respectively). Conclusions: Among older adults with UTI, the harms of long-term antibiotic prophylaxis may outweigh their benefits. Graphical Abstract: Abstract : Antibiotic prophylaxis for urinary tract infection in older patients is associated with increased, rather than decreased, risk of emergency department visit or hospitalization for infection as well as increased risk of antibiotic resistance and antibiotic-related complications.